Recall of ICU Stay in Patients Managed With a Sedation Protocol or a Sedation Protocol With Daily Interruption. Issue 10 (October 2015) - Burry, Lisa; Cook, Deborah; Herridge, Margaret; Devlin, John W.; Fergusson, Dean; Meade, Maureen; Steinberg, Marilyn; Skrobik, Yoanna; Olafson, Kendiss; Burns, Karen; Dodek, Peter; Granton, John; et al.
<x xml:space="preserve">Abstract</x> Objectives: To 1) describe factual, emotional, and delusional memories of ICU stay for patients enrolled in the SLEAP (Daily sedation interruption in mechanically ventilated critically ill patients cared for with a sedation protocol) trial; 2) compare characteristics of patients with and without ICU recall, and patients with and without delusional memories; and 3) determine factors associated with delusional memories 28 days after ICU discharge. Design: Prospective cohort. Setting: Sixteen North American medical and surgical ICUs. Patients: Critically ill, mechanically ventilated adults randomized in the SLEAP trial. Interventions: Post-ICU interviews on days 3, 28, and 90 using the validated ICU Memory Tool. Measurements and Main Results: Overall, 289 of 297 ICU survivors (97%) (146 protocolized sedation and 143 protocolized sedation plus daily interruption patients) were interviewed at least once. Because there were no differences in recall status or types of memories between the two sedation groups, we present the findings for all patients rather than by study group. On days 3, 28, and 90, 28%, 26%, and 36% of patients, respectively, reported no recall of being in the ICU (overall perception, self-reported) (p = 0.75). Mean daily doses of benzodiazepines and opioids were lower in patients with no ICU recall than those with recall (p < 0.0001 for both). Despite one third of patients reporting no recall of ICU stay on day 3, 97% and 90% reported at least one factual and one emotional memory from ICU, respectively. Emotional memories declined with time after ICU discharge, particularly panic and confusion. Delusional memories 28 days after discharge were common (70%) yet unrelated to delirium (p = 0.84), recall status (p = 0.15), total dose of benzodiazepine (p = 0.78), or opioid (p = 0.21). Delusional memories were less likely with longer duration of mechanical ventilation (odds ratio, 0.955; 95% CI, 0.91–1.00; p = 0.04). Conclusions: Recall of ICU stay and types of memories reported were not influenced by the trial sedation strategy. Lack of ICU recall and delusional memories were common after ICU discharge despite the use of sedation strategies that promoted wakefulness.